INTRODUCING DECONSTRUCTIVE INTERSECTIONALITY: THE GENERAL JURISPRUDENTIAL RAGE AGAINST RAINBOW THEORY (The Pretoria Student Law Review, 2021)
Despite South Africa’s post-modern constitutional dispensation which, at first glance, seems to celebrate and entrench substantive equality — various judgements have been passed by the Constitutional Court where the Constitution was interpreted through a formal equalitarian lens. On the one hand, substantive equality recognises and celebrates our diversity and differences whereas formal equality, on the other hand, obsesses with the idea of sameness. This constant tension between substantive and formal equality is aptly portrayed by the term ‘rainbow jurisprudence’. This term was coined by Alfred Cockrell to explain a quasi-theory depicted by the newly born South African constitutional adjudication which was lacking in substantive reasoning (which I equate to substantive equality) and the absence of a rigorous jurisprudence. He goes so far as to assimilate the finding of genuine substantive reasoning within these judgements to the possibility of touching a rainbow — a mythical task which, although alluring, seems impossible. Thus, I have identified the problem that South Africa is still submerged in rainbow jurisprudence. This can be seen through various court cases that will be discussed below, ranging from cases that were clearly decided from a formal equalitarian perspective to those which depict a wolf in sheep’s clothing seemingly substantive judgements disguising the formal equality lurking beneath.
Keywords: formal equality; substantive equality; rainbow jurisprudence; constitutional adjudication